+0  
 
0
348
2
avatar

Given the function y = -3ex + 1 , find y if x = 2.

Guest May 13, 2017
 #1
avatar
0

plug in 2 for x

 

y = -3(e)(2) + 1

y = -6e + 1

 

By e I'm assuming you're referring to the mathematical constant (~2.7)

 

y  ≈ -15.31

Guest May 13, 2017
 #2
avatar+7348 
+1

Given the function y = -3ex + 1 , find y if x = 2.

 

\(y=3e^x+1\\e=2.718281828459\\x=2\\y=3\times 2.718281828459^2+1\)

 

\(y=23.1671682968\)

 

laugh  !

asinus  May 14, 2017
edited by asinus  May 14, 2017

12 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.